Depression: current approaches to assessment and treatment. Issue 12 (19th June 2014) - Reid, Ian; Cameron, Isobel; MacGillivray, Steve
Abstract Depression is common and concerns persist regarding choice of effective treatments. Our Drug review discusses aspects of recommended management and changes in classification, followed by sources of further information and an analysis of the prescription data.